Effective breastfeeding technique and associated factors among lactating mothers in Gidan District, North-East, Ethiopia: a community-based cross-sectional study - Eskedar Getie Mekonnen; Desale Bihonegn Asmamaw; Yohannes Ayanaw Habitu; Wubshet Debebe Negash; Dawit Zenamarkos Desta (BMJ Open)
Objective To assess effective breastfeeding technique (EBT) and associated factors among lactating mothers in Gidan District, North-East Ethiopia.Design A community-based cross-sectional study.Setting Gidan District, North-East Ethiopia.Participants A total of 786 lactating mothers were included between 30 March and 29 April 2021.Outcome EBT.Methods A multistage sampling technique was employed to recruit participants. Pretested interviewer-administered questionnaires and an observational checklist were used to collect the data. Individual scores of three variables about breast feeding, namely positioning, attachment and suckling, were computed to generate the outcome variable, that is, breastfeeding technique. Binary logistic regression analyses were carried out to determine the association between independent variables and EBT. Statistical significance was declared at a value of p≤0.05 with a corresponding 95% CI.Results Overall, the prevalence of EBT was 42.9% (326/760). Having antenatal care follow-up (adjusted OR (AOR)=1.75; 95% CI 1.10 to 2.77), delivering at health institutions (hospital AOR=2.85; 95% CI 1.22 to 6.66 and health centre AOR=2.15; 95% CI 1.25 to 3.68), and receiving postpartum home visits by the health extension workers (HEWs) (AOR=2.12; 95% CI 1.55 to 2.92) were significantly associated with the practice of EBT.Conclusion The study showed that the prevalence of EBT was low. The finding highlights the importance of promoting utilisation of antenatal care follow-up, institutional delivery and postpartum home visits by HEWs, which play a substantial role in promoting EBT.